Association between history ofinterparental violence and alcoholabuse among reproductive-age women: Evidence from the Peruvian demographicand health survey - Llamo-Vilcherrez, Anita P. (2024)
Understanding the link between witnessing parental violence and alcohol abuse in Peruvian womenWitnessing violence between parents during childhood can leave deep emotional scars. This study explores whethersuch experiences are related to alcohol abuse among Peruvian women in their adult years. Using data from a nationalhealth survey in Peru, the experiences of nearly 20,000 women were analyzed to determine if witnessing violencebetween their parents during childhood was linked to alcohol problems later in life. Responses from the 2019Peruvian Demographic and Family Health Survey were examined, focusing on women’s reports of childhood exposureto violence between parents and current alcohol abuse, controlling for factors like age, education, and mental health.The study found that women who witnessed their parents engaging in violence were more likely to abuse alcoholas adults. About 41% of the women reported seeing such violence, and of these, a higher proportion struggled withalcohol compared to those who did not witness violence. Understanding the link between childhood experiences andadult behaviors can help develop targeted interventions to prevent alcohol abuse. This research highlights the needfor support systems that help women cope with the emotional impacts of childhood trauma, potentially reducingalcohol-related problems in the future.